The Effect of Entrepreneurship Leadership and Motivation on Employees' Satisfaction at Serang Raya University - Hamdan Hamdan (STKIP Singkawang, 2018)
A leader who has an entrepreneurial spirit or entrepreneurial leadership and motivation is absolutely necessary as an intangible culture, a non-physical structural capability that is able to move a physical figure, dare to take risks and prioritize work performance. so this study aims to determine the Effect of Entrepreneurship Leadership and Motivation on Employee Job Satisfaction at Serang Raya University. This study uses a descriptive method and in the form of a questionnaire distributed to 77 respondents who were the samples of this study, the data came from populations that were normally distributed and had the same variance. The technique of collecting data using a questionnaire with a Likert scale measurement. correlation coefficient R = 0.723, while the coefficient of determination seen from R Square = 0.522 which means that entrepreneurial leadership and motivation of independent variables in explaining the dependent variable by 52.2% the remaining 47.8% is influenced by other factors such as work culture, employee discipline, environment work, etc. which were not included in this study. And there is a significant influence between entrepreneurial leadership and motivation on employee job satisfaction at Serang Raya University in the t test, the results obtained t count> t table (4,281> 1,992), it can be concluded that there is a significant influence between entrepreneurial leadership (X1) and motivation (X2) on employee job satisfaction (Y) at Serang Raya University.